Potential bile acid metabolites. 23. Syntheses of 3-glucosides of nonamidated and glycine- and taurine-amidated bile acids. - T Iida; S Nishida; Y Yamaguchi; M Kodake; F C Chang; T Niwa; J Goto; T Nambara (Journal of Lipid Research, 1995)
The 3-glucosides of nonamidated lithocholic, chenodeoxycholic, ursodeoxycholic, deoxycholic, and cholic acids, and their double conjugate forms with glycine and taurine were synthesized. The key reactions used were 1) beta-D- glucosidation at C-3 by the Koenigs-Knorr condensation reaction of 3 alpha-hydroxylated bile acid methyl (or p-nitrophenyl) esters with 1 alpha-bromo-1-deoxy-2, 3, 4, 6-tetra-O-acetyl-D-glucopyranose in the presence of cadmium carbonate in refluxing benzene; 2) indirect and direct amidations at C-24 by the activated p-nitrophenyl ester and by the diethylphosphorylcyanide methods, respectively, using glycinate ester and taurine as coupling agents; and 3) simultaneous alkaline hydrolysis of the hydroxyl-protecting and ester groups in both the sugar and aglycone moieties.